2020
DOI: 10.1653/024.102.0401
|View full text |Cite
|
Sign up to set email alerts
|

Pollinia Removal and Suspected Pollination of the Endangered Ghost Orchid, Dendrophylax lindenii (Orchidaceae) by Various Hawk Moths (Lepidoptera: Sphingidae): Another Mystery Dispelled

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…50 km from the SE of the FPNWR. This study also revealed that only one of the seven sites (Population A) harbored spontaneous seedlings during all six years when data were collected, and this site was also the wettest, i.e., it maintains relatively high water levels throughout the year [ 10 ]. One site (Population D) harbored 15 seedlings that were recorded in the 2019 survey, but these seedlings did not survive the following year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…50 km from the SE of the FPNWR. This study also revealed that only one of the seven sites (Population A) harbored spontaneous seedlings during all six years when data were collected, and this site was also the wettest, i.e., it maintains relatively high water levels throughout the year [ 10 ]. One site (Population D) harbored 15 seedlings that were recorded in the 2019 survey, but these seedlings did not survive the following year.…”
Section: Discussionmentioning
confidence: 99%
“…Available moisture at Population A also may affect the hawk moth pollinators of D. lindenii by reducing the distribution of potential host plants needed by their larvae. Danaher et al [ 10 ] documented at least two hawk moth pollinators (Lepidoptera: Sphingidae) of D. lindenii in the FPNWR ( Dolba hyloeus , Pachylia ficus ) and four other species are suspected of being capable of pollination. Larvae of both D. hyloeus and P. ficus are reported to feed on Ficus and Ilex trees [ 10 ] which are probably less prone to desiccation than herbaceous plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, a mid‐range CT costs 200—500 USD (Rovero et al., 2013; Wearn & Glover‐Kapfer, 2017). The unit price of motion‐triggered CT systems designed for insect monitoring range from 400 EUR (Pegoraro et al., 2020) to several thousands of euros (Danaher et al., 2020; Houlihan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%